Feminist Economics For Behavioral Economists - Austen, Siobhan (Centre for Research in Applied Economics, 2015)
This paper attempts to elucidate key themes in feminist economics that are relevant to major concerns in behavioral economics, including gender differences in risk aversion. It makes use of the Institutional Analysis and Design (IAD) framework developed by Elinor Ostrom and her colleagues to organize this discussion. The paper examines how ideas about the structure and influence of mental models relate to a feminist critique of the standard methods used in studies of sex-based differences in behavior. It also argues that the feminist economic concept of ‘individuals-in-relation’ has the potential to guide future empirical and theoretical studies of men’s and women’s economic behavior.